2022
DOI: 10.2807/1560-7917.es.2022.27.44.2200785
|View full text |Cite
|
Sign up to set email alerts
|

Omicron BA.2.75 variant is efficiently neutralised following BA.1 and BA.5 breakthrough infection in vaccinated individuals, Israel, June to September 2022

Abstract: We evaluated neutralising antibody titres against wild type (WT) SARS-CoV-2 and four Omicron variants (BA.1, BA.2, BA.5 and BA.2.75) in fully vaccinated (three doses of Comirnaty vaccine) healthcare workers (HCW) in Israel who had breakthrough BA.1/BA5 infections. Omicron breakthrough infections in vaccinated individuals resulted in increased neutralising antibodies against the WT and Omicron variants compared with vaccinated uninfected HCW. HCW who recovered from BA.1 or BA.5 infections showed similar neutral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In addition to changing its sensitivity to antiviral drugs, this mutation might be involved in affecting the replication speed of the virus which is the basic function of the RdRp protein [ 33 ]. Further to the antiviral treatments, it has been reported that the vaccinated individuals who had suffered with some breakthrough infection from B.1, or B.5 had got protective level of (hybrid) immunity against BA.2.75 compared with those who were only vaccinated (3-doses), which shows high level of cross-immunity between B.1, B.5, and B.2.75 variants [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to changing its sensitivity to antiviral drugs, this mutation might be involved in affecting the replication speed of the virus which is the basic function of the RdRp protein [ 33 ]. Further to the antiviral treatments, it has been reported that the vaccinated individuals who had suffered with some breakthrough infection from B.1, or B.5 had got protective level of (hybrid) immunity against BA.2.75 compared with those who were only vaccinated (3-doses), which shows high level of cross-immunity between B.1, B.5, and B.2.75 variants [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…protective level of (hybrid) immunity against BA.2.75 compared with those who were only vaccinated (3-doses), which shows high level of cross-immunity between B.1, B.5, and B.2.75 variants [34].…”
Section: Plos Onementioning
confidence: 91%
“…Plasma nAb by pseudovirusneutralization assays and memory B cell by FACS Strong neutralization against both WT and BA.1; expansion of memory B cells that targeted conserved epitopes rather than BA.1-specific Atari et al, 2022 [22] Three doses of the BNT162b2 vaccine BA.1 or BA.5 infection Plasma nAb by pseudovirusneutralization assays Higher levels of plasma nAb against WT than against the infected variant Kaku et al, 2022 [23] mRNA-1273 or BNT162b2 vaccine…”
Section: Ba1 Infectionmentioning
confidence: 99%
“…[21] Similar events were also observed in donors who received the full three doses of the BNT162b2 vaccine followed by BA.1 or BA.5 breakthrough infection, in whom nAb titers against WT SARS-CoV-2 were boosted to a greater extent than those against the infected variant. [22] In another cohort of BA.1 breakthrough infection, despite prior immunization with mRNA-1273 or BNT162b2, the serum nAb titers against D614G were approximately two-fold higher than those against BA.1. At the cellular level, the frequencies of cross-reactive cells among the total peripheral anti-receptor-binding domain (RBD) B cells were 65%–83%.…”
Section: Oas During Sars-cov-2 Variantsmentioning
confidence: 99%
“…This study provides support for the notion that breakthrough infection prior to the bivalent vaccine confers higher vaccine immunogenicity than for those without a history of infection. 8 Importantly, the high neuralization efficiency immediately before the fifth vaccination for HTxRs with breakthrough infection suggests that additional research is required to explore a duration longer than 3-months after COVID-19 before the administration of the bivalent vaccine. Our data also suggest that additional protection induced by the bivalent vaccine may be expected for the general population.…”
mentioning
confidence: 99%